Plithogenic-Neutrosophic Rough Number for Reimagining Rural Education: Quality Evaluation of Early Childhood Programs - Lihong Xu; Ning Peng (Neutrosophic Sets and Systems)
Early childhood education (ECE) is crucial to rural rehabilitation because it promotes sustainable and equitable development in underprivileged areas. Using an evaluation approach, this study provides a thorough assessment of the caliber of early development programs in rural regions. Four primary characteristics are the focus of the assessment: community and family participation, curriculum relevance and delivery, teacher qualification and training, and infrastructure quality. To ascertain their efficacy and contextual fit, six different rural ECE program models, from mobile units to cooperative-funded schools, were examined using both qualitative and quantitative methods. To develop a comparison framework, the study used field observations, stakeholder comments, and performance indicators. This study uses the Plithogenic-Neutrosophic Rough Number to overcome uncertainty information. The findings show notable differences in program quality and emphasize the role that community integration, instructor readiness, and localized design play in fostering successful educational outcomes. In line with national rural regeneration aims, this study aids in the planning, policy-making, and strategic development of rural early learning environments.